Any small goodness : a novel of the barrio - Johnston, Tony, 1942- (Scholastic Signature, 2002)
Arturo and his family and friends share all kinds of experiences living in the barrio of East Los Angeles--reclaiming their names, playing basketball, championing the school librarian, and even starting their own gang.